New contributions to the knowledge of Chinese flea beetle fauna (III): revision of Meishania Chen & Wang with description of five new species (Coleoptera: Chrysomelidae: Galerucinae) - Ruan, Yongying; Konstantinov, Alexander S.; Prathapan, K. D.; Zhang, Mengna; Jiang, Shihong; Yang, Xingke (Zootaxa, 2018)
The flea beetle genus Meishania Chen & Wang is revised and five new species—M. cangshanensis sp. nov., M. flavipennis sp. nov., M. fulvotigera sp. nov., and M. sichuanica sp. nov. from China and M. bhutanensis sp. nov. from Bhutan—are described. All species of Meishania are illustrated and a key to species is provided.